LITERATURE REVIEW: FITOTERAPI UNTUK PENGOBATAN GANGGUAN SISTEM PERNAFASAN - Nawwar Irfan; Yucuely Benedika N; Astuti Damayanti; Sapna Ariani; Tirta Naila (PT. Saha Kreasi Indonesia, 2026)
Respiratory system disorders are a common condition and their prevalence continues to increase, especially in developing countries. The use of traditional medicinal plants is widely utilized as an alternative therapy because it is considered safe, easily accessible, and highly effective. The purpose of writing this article is to present a pharmacological study of medicinal plants that have the potential to be used as phytotherapy for respiratory system disorders. The method used in this study is a literature review of relevant scientific articles. The study results indicate that active compounds such as flavonoids, phenolics, terpenoids, and alkaloids possess anti-inflammatory, bronchodilator, immunomodulatory, antioxidant, and antiviral activities that play a role in improving respiratory tract function and reducing the symptoms of respiratory disorders. Medicinal plants have great potential as a complementary therapy for respiratory system disorders, although further research is needed to clinically confirm their effectiveness and safety.